Evaluasi Tarif Parkir di Tepi Jalan Umum berdasarkan Zona di Kota Pangkapinang - Revy Safitri; Ririn Amelia; Jeanne Darc Noviayanti Manik (Universitas Islam 45, 2019)
Pangkalpinang City, the Capital of Bangka Belitung province, is the center of various activity with the characteristic of high vehicle trips; therefore, the larger parking spaces are needed. The parking spaces in this city utilizes not only the parking lots but also on-street parking. The implementation of on-street parking fee policy recently has not run optimally. This study aims to evaluate the on-street parking fee in Pangkalpinang City based on the parking zone to determine appropriate parking fee. In this study, the evaluation of on-street parking fee was analyzed based on Ability To Pay (ATP) and Willingness To Pay (WTP). Result showed that the existing parking fee for motorcycle and car is too low and needs to be revised. The existing parking fee can be adjusted to more than the average real parking fee but ideally the fee should not more than the ATP value. This result can be used as a guidance for Pangkalpinang City Government to evaluate the on-street parking fee policy.